Health Surveillance in India: Current and Future Prospects - Vinoth Gnana Chellaiyan; Sasithra (Journal of Clinical and Diagnostic Research, 2021)
Surveillance is an information for action. India has created considerable improvement in control, prevention and eradication of certain communicable diseases. Few such diseases that have been effectively controlled are polio, smallpox, vector-borne illness, nipah, Coronavirus Disease-2019 (COVID-19) and so on. These achievements are the outcome of an active surveillance system incorporated at community, facility, and health system level. Any of these progresses is impossible without a robust public health surveillance structure. Therefore, enhancing the public health surveillance system further will be helpful in managing upcoming pandemics at its earliest. Improvements in public health surveillance should be synchronised with the goals of Universal Health Coverage and its regulating standards of safe guarding universal health as a right besides privilege, ensuring equity, non-discrimination, guarding the affected individual’s rights and respect their choice and placing health in people’s hand. In alignment with the National Digital Health Mission, the new Integrated Health Information Platform (IHIP) aims to substitute traditional surveillance data-entry system with modern advances in digital health and technology. This platform also initiates various sector collaboration, including public and private healthcare organisations and civil societies. Recommendations to strengthen the surveillance system starts with enhancement of laboratory infrastructure, referral networks and health organisations at the block level with the aim of strengthening community-based surveillance and responding in a timely manner for upcoming outbreaks.